2017
DOI: 10.3390/su9122281
|View full text |Cite
|
Sign up to set email alerts
|

Do Sustainable Procurement Practices Improve Organizational Performance?

Abstract: This exploratory study investigates the impacts of sustainable procurement (SP) practices on organizational performance by using the established scales of SP practices and organizational performances, taking Saudi Arabia as a case country. Data used in the study was collected through a questionnaire survey from procurement directors and managers. Regression and multivariate-based path analysis was performed to assess the impacts of SP practices. From the preliminary results, a significant association between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 33 publications
4
27
0
Order By: Relevance
“…Islam, et al [52] assessed the impacts of sustainable procurement (SP) practices on organisational performance. The study found that, there is a positive relationship between sustainable procurement and service delivery.…”
Section: Sustainable Procurement Practices and Service Deliverymentioning
confidence: 99%
“…Islam, et al [52] assessed the impacts of sustainable procurement (SP) practices on organisational performance. The study found that, there is a positive relationship between sustainable procurement and service delivery.…”
Section: Sustainable Procurement Practices and Service Deliverymentioning
confidence: 99%
“…Cronbach's alpha coefficient ranges from 0 to 1.00, where 1.00 indicates the highest level of validity and reliability of the quantitative inputs [43]. Previous studies suggest that alpha scores above 0.70 are considered acceptable and, since Cronbach's alpha value is above 0.886, the scale in this study is considered reliable and indicated that each item was unique and not a repetition [50], [60].…”
Section: Theoretical Backgroundmentioning
confidence: 75%
“…The authors of [49] stated that it 'involves the purchase of any product or service that results in a lesser environmental impact while performing a similar function (to comparable products or services) and while demonstrating social responsibility and ethics, at its comparable price to enhance competitive performance'. Despite the growing inclusion of sustainable criteria in the procurement processes [18], [50], and the broader attention received by researchers worldwide [21], in many cases, however, the focus was on only one of the three pillars [40], tending to favor the environmental dimension [51], thus dismantling the concept of SPP.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…These include various fields of business administration and, primarily, supply chain management (e.g. Thorlaksona, de Zegherb and Lambin, 2018;Meehan and Bryde, 2011;Islam et al, 2017). Walker et al (2012) have documented the growing interest of management studies into sustainable procurement.…”
Section: Literature Reviewmentioning
confidence: 99%